Engineered Nanoplatelets for Targeted Delivery of Plasminogen Activators to Reverse Thrombus in Multiple Mouse Thrombosis Models. Issue 4 (1st December 2019) - Xu, Junchao; Zhang, Yinlong; Xu, Jiaqi; Liu, Guangna; Di, Chunzhi; Zhao, Xiao; Li, Xiang; Li, Yao; Pang, Ningbo; Yang, Chengzhi; Li, Yanyi; Li, Bozhao; et al.
Abstract: Rapid cut‐off of blood supply in diseases involving thrombosis is a major cause of morbidity and mortality worldwide. However, the current thrombolysis strategies offer limited results due to the therapeutics' short half‐lives, low targeting ability, and unexpected bleeding complications. Inspired by the innate roles of platelets in hemostasis and pathological thrombus, platelet membrane‐camouflaged polymeric nanoparticles (nanoplatelets) are developed for targeting delivery of the thrombolytic drug, recombinant tissue plasminogen activator (rt‐PA), to local thrombus sites. The tailor‐designed nanoplatelets efficiently accumulate at the thrombi in pulmonary embolism and mesenteric arterial thrombosis model mice, eliciting a significantly enhanced thrombolysis activity compared to free rt‐PA. In addition, the nanoplatelets exhibit improved therapeutic efficacy over free rt‐PA in an ischemic stroke model. Analysis of in vivo coagulation indicators suggests the nanoplatelets might possess a low risk of bleeding complications. The hybrid biomimetic nanoplatelets described offer a promising solution to improve the efficacy and reduce the bleeding risk of thrombolytic therapy in a broad spectrum of thrombosis diseases. Abstract : Tailor‐designed platelet membrane‐camouflaged polymeric nanoparticles (designated as nanoplatelet) for targeting delivery of the thrombolytic drug (rt‐PA) are developed to navigate multiple acute thrombosis diseases. This nanoplatform can efficiently target to clot sites and dissolve thrombus, simultaneously overcoming the main disadvantages of existing thrombolysis therapy (i.e., life‐threatening bleeding risk, a narrow therapeutic time window, and extremely low drug circulation time).